PERSEKUTUAN BANSER DAN APARAT NEGARA DALAM PERISTIWA NINJA DI JAWA 1998-1999 M - Zakiyatul Khusna; Abdur Rahman; Fathul Qorib (Batuthah: Jurnal Sejarah Padaban Islam, 2024)
This research analyzes the contribution of Barisan Ansor Serbaguna (Banser) in dealing with ninja incidents that occurred in society in 1998-1999. The main focus of the research is on the correlation of interactions between Banser and state officials in responding to and resolving the ninja incident in 1998. Using qualitative research, this research explores information through in-depth interviews, data documents, and analysis of related documents. The main findings show that Banser had a significant role in maintaining societal stability during the Ninja incident. Cooperation between Banser and state officials had a positive impact in dealing with the crisis. A good correlation between the two increases the effectiveness of preventive and responsive actions, which ultimately helps restore social order. This provides deeper insight into the role of security organizations such as Banser in supporting the tasks of state officials in facing complex challenges at the community level. The implications of these findings can be a basis for developing better collaborative strategies between community organizations and government in overcoming similar crisis situations in the future.